Fermented Soy and Fish Protein Dietary Sources Shape Ileal and Colonic Microbiota, Improving Nutrient Digestibility and Host Health in a Piglet Model - Li, Ying; Han, Yunsheng; Zhao, Qingyu; Tang, Chaohua; Zhang, Junmin; Qin, Yuchang (Frontiers in Microbiology, 2022)
Suitable protein sources are essential requirements for piglet growth and health. Typically, intestinal microbiota co-develops with the host and impact its physiology, which make it more plastic to dietary protein sources at early stages. However, the effects of fermented soybean meal (FSB) and fish meal (FM) on foregut and hindgut microbiota, and their relationship with nutrient digestion and host health remain unclear. In this study, we identified interactions between ileac and colonic microbiota which were reshaped by FSB and FM, and assessed host digestibility and host health in a piglet model. Eighteen weaned piglets (mean weight = 8.58 ± 0.44 kg) were divided into three dietary treatments, with six replicates/treatment. The level of dietary protein was 16%, with FSB, FM, and a mixture of fermented soybean meal and fish meal (MFSM) applied as protein sources. During days 1–14 and 1–28, diets containing MFSM generated higher piglet body weight and average daily gain, but lower feed to weight gain ratios when compared with the FM diet (P < 0.05). Piglets in MFSM and FM groups had lower apparent total tract digestibility (ATTD) of crude protein (CP) compared with the FSB group (P < 0.05). Serum immunoglobulins (IgM and IgG) in MFSM and FM groups were significantly higher on day 28, but serum cytokines (interleukin-6 and tumor necrosis factor-α) were significantly lower than the FSB group on days 14 and 28 (P < 0.05). When compared with FSB and FM groups, dietary MFSM significantly increased colonic acetic acid and butyric acid levels (P < 0.05). Compared with the FM and MFSM groups, the FSB diet increased the relative abundance of ileac Lactobacillus and f_Lactobacillaceae, which were significant positively correlated with CP ATTD (P < 0.05). Compared with the FSB group, the relative abundance of f_Peptostreptococcaceae and Romboutsia in MFSM or FM groups were increased and were significant positively correlated with total carbohydrate (TC) ATTD (P < 0.05). Piglets fed FSB had higher α-diversity in colonic microbiota when compared with other groups (P < 0.05). The relative abundance of colonic unidentified_Clostridiales and Romboutsia in MFSM and FSB groups were significantly higher than in the FM group (P < 0.05). Dietary MFSM or FM increased the relative abundance of colonic Streptococcaceae and Streptococcus, but decreased the relative abundance of Christensenellaceae when compared with the FSB group (P < 0.05). These bacteria showed a significantly positive correlation with serum cytokine and immunoglobulin levels (P < 0.05). Therefore, dietary FSB improved CP digestibility by increasing the relative abundance of ileac f_Lactobacillaceae and Lactobacillus, while dietary MFSM benefited TC digestibility by increasing f_Peptostreptococcaceae and Romboutsia. Dietary MFSM and FM enhanced immunoglobulin secretion by increasing colonic f_Streptococcaceae and Streptococcus prevalence, while dietary FSB promoted cytokine production by increasing microbiota diversity and Romboutsia and Christensenellaceae. Our data provide a theoretical dietary basis for young animals using plant and animal protein sources.